The Traveller; Versified Translation of the Persian Poem "Musafir" - Iqbal, Allama; Translated by Jamil Naqvi (Karachi Royal Book Company, 1991)
Living account for living people.
This poem is translated by Jamil Naqvi.
Keywords: Iqbaliyat -- Persian -- Musafir -- Allama Iqbal -- The Traveller -- The Traveler